Proposta para implementação de um planejamento estratégico em uma empresa de serviços do ramo de beleza - FERREIRA, Aressa Aparecida Ribeiro (2019)
The present work aimed at a proposal for the implementation of a Strategic Planning for Espaço de Beleza Estilo Ltda. and in order to achieve this objective, the internal and external environment of the company was analyzed, the organizational guidelines were drawn up, and a plan of action for the implementation of actions that could be carried out by the company under analysis. To obtain a diagnosis, data collection, interviews, bibliographic research and regional research were used as tools, such as: studies and analyzes of competitors, clients and also suppliers, among other means to obtain what is necessary for the preparation of the EP. The owner of the establishment was the researcher. In addition, an action plan, with the PDCA cycle, was drawn up to be implemented by the EP on the basis of the results achieved. In order to do so, one can affirm the importance that strategic planning presents, mainly, to outline the strategies to be followed and the decision-making that must be carried out to reach the objectives determined by the organization in a market that undergoes constant changes.